Sampul Depan, Daftar Isi, Kata Pengantar - Daftar Isi, Kata Pengantar, Sampul Depan (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
Sampul Depan, Daftar Isi, Kata Pengantar